1981
DOI: 10.1016/0006-8993(81)90919-7
|View full text |Cite
|
Sign up to set email alerts
|

α2-Adrenoreceptors in rat brain are decreased after long-term tricyclic antidepressant drug treatment

Abstract: After two weeks of twice-daily administration of amitriptyline to rats, the binding of [3H]clonidine to presynaptic alpha 2-adrenoreceptors was decreased in membranes isolated from 5 areas of the rat brain. After one day of treatment, binding did not differ from saline treated controls. In vitro, a high concentration of amitriptyline caused a competitive inhibition of [3H]clonidine binding but did not alter the number of binding sites. The decrease in the number of alpha 2-adrenoreceptor binding sites after tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(62 citation statements)
references
References 15 publications
3
58
1
Order By: Relevance
“…[15][16][17]19,65 In the human brain, chronic antidepressant treatment seems to downregulate ␣ 2A -adrenoceptors in depressed suicide victims. 11 Nevertheless, the enhanced immunoreactive levels of the ␣ 2A -adrenoceptor protein in depressed suicide victims remain more resistant to downregulation by antidepressants.…”
Section: Molecular Psychiatrymentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17]19,65 In the human brain, chronic antidepressant treatment seems to downregulate ␣ 2A -adrenoceptors in depressed suicide victims. 11 Nevertheless, the enhanced immunoreactive levels of the ␣ 2A -adrenoceptor protein in depressed suicide victims remain more resistant to downregulation by antidepressants.…”
Section: Molecular Psychiatrymentioning
confidence: 99%
“…14 Many antidepressant treatments are able to modulate ␣ 2 -adrenoceptor density and/or function. Thus, chronic administration of antidepressant drugs reduces the density and activity of ␣ 2 -adrenoceptors in rat brain [15][16][17][18][19] and in platelets of depressed patients. 20,21 Based on these observations, it has been suggested that patients with mood disorders might have an underlying disturbance of noradrenergic and/or serotonergic function, perhaps due to hyperactive ␣ 2 -adrenoceptor function.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, stimulation of presynaptic a 2 -and 5-HT-autoreceptors induce a decrease in the synthesis and release of norepinephrine and 5-HT (Esteban et al, 1999). Further evidence of the involvement of a 2 -adrenoceptors and 5-HT receptors in the pathophysiology of suicide and depression is that chronic antidepressant administration reduces the density and activity of these receptors in rat brain (Esteban et al, 1999;Invernizzi et al, 2001;Smith et al, 1981;Sibug et al, 1998;Subhash and Jagadeesh, 1997), and in the platelets of depressed subjects (García-Sevilla et al, 1986;Stahl, 1994;Sargent et al, 1997). Based on these observations, it has been suggested that patients with mood disorders might suffer an underlying disturbance of noradrenergic and/or serotonergic function.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, suicide victims treated with antidepressants have however significantly lower levels of α 2 -adrenoceptors in cortex, hippocampus, caudate and amygdala compared to antidepressant-free suicides (De Paermentier et al, 1997). Chronic antidepressant treatment has also repeatedly been shown to induce down-regulation of α 2 -adrenoceptors in rat brain (Barturen and Garcia-Sevilla, 1992;Cottingham et al, 2011;Smith et al, 1981). However, it must be noted that post-mortem changes in binding do not always correlate with the in vivo functional response of receptors and increased sensitivity of amygdaloid neurons to monoaminergic transmitters has been found following antidepressant treatment (Wang and Aghajanian, 1980).…”
Section: Discussionmentioning
confidence: 99%